The Impact of Maturation Medium Supplemented with PMSG and HCG Hormones on In vitro Maturation of Ovine Oocytes - Fatma Baiomy; Ahmed Kamel; Abdelhadi Hussein; Sabry Hassanin (Journal of Applied Veterinary Sciences)
This investigation aimed to assess the dose-dependent impact of the pregnant mare serum gonadotropin (PMSG) on the in vitro maturation of sheep oocytes and the effect of combining the best dose with the human chorionic gonadotropin (hCG), which is a cost-effective substitute for FSH and LH hormones. The study was planned as two experiments that included 1134 oocytes to study the impact of varying concentrations (0, 10, 20, and 40 IU/mL) of PMSG addition (1st experiment) as well as the influence of hCG, PMSG, or their combination (2nd experiment) on the ovine’s oocyte in vitro. The experimental groups of the 2nd experiment were control (G1), 20 IU/mL hCG (G2), 20 IU/mL PMSG (G3), and 20 IU/mL PMSG plus 20 IU/mL hCG (G4). The first experiment demonstrated that the polar body (PB) rate was increased (P < 0.01) by all treated groups, being 13.33, 17.76, and 15.70 in G2, G3, and G4 versus 9.87% in G1, respectively. The mitochondrial fluorescent intensity recorded 7.61, 11.92, 12.43, and 12.35, while the lipid fluorescent intensity was 9.88, 29.98, 40.05, and 25.66 for G1, G2, G3, and G4, respectively, being higher (P < 0.05) in treatment groups than in the control one. The results of the 2nd experiment showed that the PB extrusion was higher (P < 0.01) in G2, G3, and G4 than in G1 (12.60, 14.91, and 14.75 vs. 6.92%, respectively). The mitochondrial fluorescent intensity recorded 8.82, 12.30, 17.58, and 13.36 for G1, G2, G3, and G4, respectively. The lipid fluorescent intensity was 10.16, 6.98, 13.83, and 49.68 for G1, G2, G3, and G4, respectively. In conclusion, the addition of PMSG and hCG to sheep oocyte maturation media improved the oocyte maturation.